Pleiotropic Effects of Glucocorticoids on the Immune System in Circadian Rhythm and Stress - Shimba, Akihiro; Ejima, Aki; Ikuta, Koichi (Frontiers in Immunology, 2021)
Glucocorticoids (GCs) are a class of steroid hormones secreted from the adrenal cortex. Their production is controlled by circadian rhythm and stress, the latter of which includes physical restraint, hunger, and inflammation. Importantly, GCs have various effects on immunity, metabolism, and cognition, including pleiotropic effects on the immune system. In general, GCs have strong anti-inflammatory and immunosuppressive effects. Indeed, they suppress inflammatory cytokine expression and cell-mediated immunity, leading to increased risks of some infections. However, recent studies have shown that endogenous GCs induced by the diurnal cycle and dietary restriction enhance immune responses against some infections by promoting the survival, redistribution, and response of T and B cells via cytokine and chemokine receptors. Furthermore, although GCs are reported to reduce expression of Th2 cytokines, GCs enhance type 2 immunity and IL-17-associated immunity in some stress conditions. Taken together, GCs have both immunoenhancing and immunosuppressive effects on the immune system.